Network governance at the firm and network level: Goals, routines, and social mechanisms - Gerrit W. Ziggers; Taras Gagalyuk; Jon Hanf (International Journal on Food System Dynamics, 2010)
This article contributes to the general understanding of governance in networks and the achievement of private and common goals. Integrating transaction costs and social network theory, a simple integrated framework is provided for understanding why firms collaborate and under which conditions they establish durable networks that succeed in achieving goals. Network theory is extended by explicitly distinguishing between firm and network level governance, and by identifying governance mechanisms that adapt, coordinate, and safeguard customized exchanges. This way issues as how networks evolve, how they are governed, and ultimately, how collective outcomes might be generated can be better comprehended. This is especially relevant to policy planners and those having a perspective that goes beyond the performance of individual organizations.
Keywords: 330; network governance; social network theory; governance mechanisms